Current challenges and therapeutic advances of CAR-T cell therapy for solid tumors - Tong Chen; Mingzhao Wang; Yanchao Chen; Yutao Liu (Cancer Cell International, 2024)
Abstract The application of chimeric antigen receptor (CAR) T cells in the management of hematological malignancies has emerged as a noteworthy therapeutic breakthrough. Nevertheless, the utilization and effectiveness of CAR-T cell therapy in solid tumors are still limited primarily because of the absence of tumor-specific target antigen, the existence of immunosuppressive tumor microenvironment, restricted T cell invasion and proliferation, and the occurrence of severe toxicity. This review explored the history of CAR-T and its latest advancements in the management of solid tumors. According to recent studies, optimizing the design of CAR-T cells, implementing logic-gated CAR-T cells and refining the delivery methods of therapeutic agents can all enhance the efficacy of CAR-T cell therapy. Furthermore, combination therapy shows promise as a way to improve the effectiveness of CAR-T cell therapy. At present, numerous clinical trials involving CAR-T cells for solid tumors are actively in progress. In conclusion, CAR-T cell therapy has both potential and challenges when it comes to treating solid tumors. As CAR-T cell therapy continues to evolve, further innovations will be devised to surmount the challenges associated with this treatment modality, ultimately leading to enhanced therapeutic response for patients suffered solid tumors.